UCHINCHI RENESSANS - YOSHLAR NAZARIDA - Hamrayeva, Aziza (Maktabgacha taʼlim jurnali, 2022)
The purpose of this article is to analyze the issues of establishing the Third Renaissance, radically reforming the education system and raising the morale of young people, as well as to promote the effective use of opportunities created for young peop